How coloniality generated religious illiteracy in Africa, and how to compensate the situation: Perspectives on Lesotho - Mokotso, Rasebate I. (HTS teologiese studies, 2021)
This article debated how coloniality created religious illiteracy in Lesotho. Three parameters were suggested in this regard. Firstly, it is assumed that the prevalence of religious illiteracy started during missionary involvement in Lesotho. Secondly, it is argued that three strategies were applied in this exertion: (1) the missionaries categorised Basotho as being without religion and, therefore, are liable for conversion into religion, which is Christianity. This predisposition ended up in the creation of religion synonymic to Christianity whilst all others disqualified, (2) Basotho were enticed into the binary of religious secularism and privatisation disassociated from spiritualism whilst connected to materialism and private affairs and (3) Basotho were indoctrinated into accepting the existence of one universal religion which is Christianity through Western formal education. Thirdly and finally, decoloniality turn is recommended to curtail illiteracy in religion through the ontology of pluriversality, the hegemony of diversality and the epistemology of pluriversality.Contribution: The article identified the pervasiveness of religious illiteracy in Africa with special reference to Lesotho. It highlighted its repercussions if left unchecked. Consequently, it examined and put forward the possible causes. As a result of the discoveries, the article suggested procedures to counter the causes in order to promote literacy in religion.